Efektivitas Layanan Konseling Kelompok Dengan Teknik Self Management Untuk Mereduksi Kecanduan Negatif Tiktok Pada Siswa Kelas IX B Di SMP 4 BAE - Firda Auliyatul Khasanah; Arista Kiswantoro; Indah Lestari (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
Group counseling is a guidance service that helps students address problems through group interaction. One common issue is TikTok addiction, which disrupts learning focus, task completion, and academic performance. This study explores the use of group counseling with a self-management technique to reduce TikTok addiction among Grade IX B students at SMP 4 Bae. A quantitative approach was applied using a quasi-experimental method with a non-equivalent control group design. Two groups participated: an experimental group (received treatment) and a control group (no treatment), both given pretests and posttests. Data were collected through interviews, observation, and a TikTok addiction scale, then analyzed using the Wilcoxon signed-rank test. Results showed a significant decrease in addiction scores in the experimental group (from 134.4 to 79.63), while the control group showed a smaller reduction (from 132.75 to 119.63). This while indicates that group counseling with a self-management technique is effective in reducing TikTok addiction.